2016
DOI: 10.1002/ajmg.a.37611
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive MFN2‐related Charcot‐Marie‐Tooth disease with diaphragmatic weakness: Case report and literature review

Abstract: Pathogenic variants in the mitofusin 2 gene (MFN2) are the most common cause of autosomal dominant Charcot-Marie-Tooth (CMT2) disease, which is typically characterized by axonal sensorimotor neuropathy. We report on a 7-month-old white female with hypotonia, motor delay, distal weakness, and motor/sensory axonal neuropathy in which next-generation sequencing analysis identified compound heterozygous pathogenic variants (c.2054_2069_1170del and c.392A>G) in MFN2. A review of the literature reveals that sporadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Given that capnographic data from sleep studies in CMT1A patients are not yet available, sleep‐related breathing has only been systematically evaluated with regard to intermittent upper airway collapse, that is, obstructive sleep apnea . Thus, current evidence suggests that severe diaphragm weakness is rare in CMT1A, which is in clear contrast with other genetic subtypes that may be associated with respiratory failure already in childhood . However, phrenic nerve involvement with variable impact on diaphragm function may be present as outlined above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that capnographic data from sleep studies in CMT1A patients are not yet available, sleep‐related breathing has only been systematically evaluated with regard to intermittent upper airway collapse, that is, obstructive sleep apnea . Thus, current evidence suggests that severe diaphragm weakness is rare in CMT1A, which is in clear contrast with other genetic subtypes that may be associated with respiratory failure already in childhood . However, phrenic nerve involvement with variable impact on diaphragm function may be present as outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…22 We observed that mean dCMAP amplitude did not significantly differ between [51][52][53] Thus, current evidence suggests that severe diaphragm weakness is rare in CMT1A, which is in clear contrast with other genetic subtypes that may be associated with respiratory failure already in childhood. 54 However, phrenic nerve involvement with variable impact on diaphragm function may be present as outlined above.…”
Section: Phrenic Nerve Involvement In Cmt1amentioning
confidence: 99%
“…[ 39 ] Thus, MFN2 may be involved in different pathophysiological processes in different systems. [ 40 41 42 ] Further studies are necessary to determine if this effect is present in other types of immune cells. Second, MFN2 may mediate different effects in T cells under different stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical findings included hearing loss, lipodystrophy, vocal cord palsy, tongue hypertrophy, and facial and respiratory muscle weakness. Heterozygous carrier parents showed no or minimal symptoms [157,[161][162][163][164][165][166][167][168][169][170][171][172].…”
Section: Mfn2mentioning
confidence: 99%